Film agency funding in Australia : government assistance to the Australian film industry through federal and state agencies to June 2002. (Australian Film Commission, 2004)
This report lays the foundations for a better appreciation of the importance of direct assistance in the complex matrix of investment, incentives, subsidies and regulation that must underpin the continuing development of a healthy screen production industry capable of fulfilling both cultural and economic outcomes.